ПСИХОЛОГИЧЕСКИЕ ОСОБЕННОСТИ ВЗАИМОДЕЙСТВИЯ В ФУТБОЛЬНЫХ КОМАНДАХ - Sultonv, Baxtiyor (Физическое воспитание, спорт и здоровье, 2022)
Summary. The article considers the ability to work in a team. The article highlights the psychological peculiarities of the development of the ability to work in a sports team of adolescents and youths playing football.